Pengaruh Model Pembelajaran ECIRR dan PQ4R terhadap Kemampuan Pemecahan Masalah Matematis Ditinjau dari Self Efficacy - Septianingsih, Rika; Netriwati, Netriwati; Gunawan, Wawan (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2022)
This research is motivated by the low mathematical problem solving ability of students where the learning process is still teacher-centered which causes students to become passive, so an appropriate learning model is needed in the learning process. This study aims to determine the effect of differences in the use of the ECIRR and PQ4R learning models on mathematical problem solving abilities in terms of students' self-efficacy. The method used in this research is Quasi Experimental Design. The population in this study were seventh grade students of SMP Darul Ulum Sekampung. Sampling using Cluster Random Sampling. It was obtained that class VII.2 as the experimental class 1 used the ECIRR model, class VII.1 as the experimental class 2 used the PQ4R model, and class VII.3 as the control class used the Direct Instruction model with fractional material. Data collection techniques using tests, questionnaires, and documentation. Hypothesis testing using a two-way ANOVA (Analysis of Variance) test of unequal cells with a significance level of 5%. Based on the results of the study, it was concluded that (1) there was an effect of differences in the use of the ECIRR learning model, the PQ4R learning model, and the Direct Instruction model on mathematical problem solving abilities, (2) there was an effect of mathematical problem solving abilities among students who had high self-efficacy, moderate , and low, and (3) there is no interaction between the ECIRR and PQ4R learning models with self efficacy on students' mathematical problem solving abilities.